EKSPLORASI BAKTERI PELARUT FOSFAT DI LAHAN GAMBUT BERENG BENGKEL, KALIMANTAN TENGAH (Phosphate Solubilizing Bacteria Eksploration in Peatland Bereng Bengkel, Central Kalimantan) - W., Krestina (Universitas Palangka Raya, 2018)
ABSTRACTÂ The high availability of organic compounds in peatlands is stored capital and can be converted into elements by soil microbe. The high organic content causes nutrients in the soil cannot be directly utilized by plants. Phosphate solubilizing bacteriaare soil bacteria that capable ofsolubilizingphosphate, turns it into an available form in the soil. The aims of this research are to discover the existence of a phosphate solubilizing bacteriagenus and obtain potential pure isolates from Bereng Bengkel peatland, Central Kalimantan. Bacteria isolation usingselective media Pikovskaya with pour plate method. The isolation results are five phosphate solvent bacterial isolates (BPF1, BPF2, BPF3, BPF4, BPF5) which form hallozone. Based on the characterization results refering to the Bergeys Manual of Determinative of Microorganism through macroscopic observation, microscopic observation and physiological testing. BPF1 and BPF5 isolates were the genus Rhodococcusgenus, BPF2 isolates were theRhizobiumgenus, BPF3 isolates were the Micorococcusgenus, BPF4 isolates were the SerratiagenusÂ Â Keywords: Phosphate solubilizing bacteria, peatland, soil bacteria